Exact Baker–Campbell–Hausdorff formula for the contact Heisenberg algebra. (6th February 2017) - Bravetti, Alessandro; Garcia-Chung, Angel; Tapias, Diego
Abstract: In this work we introduce the contact Heisenberg algebra which is the restriction of the Jacobi algebra on contact manifolds to the linear and constant functions. We give the exact expression of its corresponding Baker–Campbell–Hausdorff formula. We argue that this result is relevant to the quantization of contact systems.